2019
DOI: 10.3390/en12193789
|View full text |Cite
|
Sign up to set email alerts
|

Optimization Design of Injection Strategy for Surfactant-Polymer Flooding Process in Heterogeneous Reservoir under Low Oil Prices

Abstract: Surfactant–polymer (SP) flooding has significant potential to enhance oil recovery after water flooding in mature reservoirs. However, the economic benefit of the SP flooding process is unsatisfactory under low oil prices. Thus, it is necessary to reduce the chemical costs and improve SP flooding efficiency to make SP flooding more profitable. Our goal was to maximize the incremental oil recovery of the SP flooding process after water flooding by using the equal chemical consumption cost to ensure the economic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…64 The experimental results showed that the polymer stored in the porous medium after polymer flooding could promote the EOR performance of the subsequent SP flooding, which increased the recovery increment by an additional 10% OOIP. 65 The SP flooding injection strategy was optimized by He et al 9 The EOR efficiency attained by different injection procedures was examined in a series of sand-packed flooding tests. The injection strategies were classified as alternating polymer and surfactant-polymer injection and simultaneous surfactant and polymer injection, with an EOR of 39.86% and 30.6%, respectively.…”
Section: Injection Strategy For Sp Floodingmentioning
confidence: 99%
See 1 more Smart Citation
“…64 The experimental results showed that the polymer stored in the porous medium after polymer flooding could promote the EOR performance of the subsequent SP flooding, which increased the recovery increment by an additional 10% OOIP. 65 The SP flooding injection strategy was optimized by He et al 9 The EOR efficiency attained by different injection procedures was examined in a series of sand-packed flooding tests. The injection strategies were classified as alternating polymer and surfactant-polymer injection and simultaneous surfactant and polymer injection, with an EOR of 39.86% and 30.6%, respectively.…”
Section: Injection Strategy For Sp Floodingmentioning
confidence: 99%
“…At the same time, the appearance of the oil leakage zone and water channeling channel led to poor sweep efficiency, so secondary oil recovery did not have a high recovery. 9,10 However, after these two stages of oil recovery, more than 50% of the crude oil is waiting to be developed. 11,12 Therefore, a tertiary oil recovery technology called chemical flooding, which has a higher oil recovery efficiency than primary oil recovery and secondary oil recovery, is gradually emerging.…”
Section: Introductionmentioning
confidence: 99%
“…Water flooding is a commonly used secondary recovery method in the industry because it is economically advantageous for the development of oil reservoirs; however, more than 60% of the heavy oil in place is usually still left after the technique is conducted [5,6]. Polymer flooding is a technology wherein high-molecular-weight, water-soluble polymers are added to the injection water to increase the viscosity and reduce the mobility ratio of the injection water and the crude oil to be displaced [7,8]. One of the most commonly used polymers is the partially hydrolyzed polyacrylamide (HPAM) due to its rapidly soluble and large hydrodynamic volume, which could greatly enhance solution viscosity.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, due to high demand for energy, polymer flooding has been successfully applied in offshore oil production in China [16][17][18][19]. As the development of the oil field, the main objectives of polymer flooding turns into type II formation, which has strong vertical heterogeneity between layers, and the physical properties between the high-permeability and low-permeability layer differ greatly [20][21][22]. Currently, under the low oil price, more recovery efficiency of polymer flooding is required, not only for the heterogeneous reservoir development, but also for heavy oil and offshore polymer flooding.…”
Section: Introductionmentioning
confidence: 99%
“…The higher the viscosity, the better the displacement effect. Studies have shown that the heterogeneity between layers, and the physical properties between the high-permeability and lowpermeability layer differ greatly [20][21][22]. Currently, under the low oil price, more recovery efficiency of polymer flooding is required, not only for the heterogeneous reservoir development, but also for heavy oil and offshore polymer flooding.…”
Section: Introductionmentioning
confidence: 99%